Factors Affecting the Adoption of High-Tech Innovations in Farming Shutchi Catfish. The Case Study of Can Tho City, Vietnam - NGUYEN, Thi Nghia; NGUYEN, The Kien (Journal of Environmental Management and Tourism; Vol 13 No 5 (2022): JEMT, Volume XIII, Issue 5(61), Fall 2022DO - 10.14505/jemt.v13.5(61).20, 2022)
Vietnam’s catfish farm is an important agricultural sector that generates over 1 million tons of food every year. The application of high-tech innovations is essential for the quick and sustainable development of catfish farm in Vietnam. However, there are both enablers and constraints that effects the decision of Vietnamese catfish farmers in applying new technology. This study aims to analyze the current situation and factors impacting farmers’ adoption of new high-tech innovations in farming Shutchi catfish at Can Tho city, Vietnam. Analyzing data from 120 Shutchi catfish farming households with the logistic regression, our results show that farming area, educational background of farmers, local government support, and local authority’s training have positive influence in the decision of farmers in accepting high-tech innovations, while number of farming years is a constraint of this process. The outcome would serve as the basis for proposals and recommendations to local authorities in order to enhance the effectiveness of promoting high-tech application in the farming of Shutchi catfish in Can Tho City, Vietnam.